2021
DOI: 10.31580/apss.v8i2.1909
|View full text |Cite
|
Sign up to set email alerts
|

The Foreign Language Students’ Readiness on Online Learning in Malaysia

Abstract: Since the COVID-19 outbreak had crossed the globe and wreaking havoc on people’s life and health, almost all educational institutions were closed down temporarily and online learning has replaced previously conducted conventional teaching and learning in the classroom. However, the main concern here is to what extent the students are ready for this drastic change in their learning endeavors. Therefore, this study seeks to examine the readiness levels of online learning among foreign language students in select… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…In Malaysia, it was found that internet literacy among undergraduate students is prominent, but self-learning motivation was reportedly at low levels (Allam et al, 2020). A study conducted by Ismail et al (2021) jointly revealed that the readiness of students in two Malaysian universities was the highest, meaning that students were ready for full-scale online learning, but lacked self-control as they were easily distracted by other online attractions, such as gaming.…”
Section: Background Of Studymentioning
confidence: 99%
“…In Malaysia, it was found that internet literacy among undergraduate students is prominent, but self-learning motivation was reportedly at low levels (Allam et al, 2020). A study conducted by Ismail et al (2021) jointly revealed that the readiness of students in two Malaysian universities was the highest, meaning that students were ready for full-scale online learning, but lacked self-control as they were easily distracted by other online attractions, such as gaming.…”
Section: Background Of Studymentioning
confidence: 99%
“…The pandemic that took place in 2020 has triggered the acceleration of online learning, and since then, those involved in teaching are obliged to deliver classes online. Ismail et. al (2021) conducted a study on seeking learners' readiness on online learning, specifically in foreign language.…”
Section: Background Of Studymentioning
confidence: 99%
“…Another area that is worth investigating in relation to online engagement among learners, research on technical supports could also assist those involved in finding out their level of engagement. As mentioned by Ismail, Saaludin, Mohd Ali & Zainal Abidin (2021), students are well-prepared in facing online learning, as they possess high level of confidence in computer.…”
mentioning
confidence: 99%
“…Due to the COVID-19 pandemic, many things have changed. This pandemic has had a detrimental impact on global economic development and social events, particularly in education (Ismail et al, 2021;Ming et al, 2021). Most of the classes, if not all, are being conducted online due to the standard operative procedures that the Malaysian Government has set.…”
Section: Introduction Research Background and Significance Of Studymentioning
confidence: 99%